Unsuccessful in Alfredo Stroessner’s Political Economy: Reynolds Metals’ Investment Attempt in Paraguay (1974-1982) (Revista Científica UCOM Scientia, 2023)
The article delves into an instance of unsuccessful foreign investment in Paraguay: Reynolds Metals’ attempt to construct a ~$700 million USD aluminum smelter during the 1970s and 1980s. It challenges conventional claims that the project’s failure stemmed solely from unsettled bribery, instead proposing that Alfredo Stroessner's broader political and economic agendas played a role. It advances a theory as to why electro-intensive industries were not established in Paraguay, despite its renewable energy surplus from hydroelectric sources in the latter half of the 20th century.
Keywords: Reynolds Metals, U.S. State Department, ANDE, hydroelectricity, foreign direct investment (FDI), industrialization